2023
DOI: 10.3389/fnins.2022.997377
|View full text |Cite
|
Sign up to set email alerts
|

Ear-EEG sensitivity modeling for neural sources and ocular artifacts

Abstract: The ear-EEG has emerged as a promising candidate for real-world wearable brain monitoring. While experimental studies have validated several applications of ear-EEG, the source-sensor relationship for neural sources from across the brain surface has not yet been established. In addition, modeling of the ear-EEG sensitivity to sources of artifacts is still missing. Through volume conductor modeling, the sensitivity of various configurations of ear-EEG is established for a range of neural sources, in addition to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 50 publications
1
5
0
Order By: Relevance
“…Further investigation of seizure types revealed that ear-EEG reliably captures temporal lobe seizures (86% for intracranial patients and 100% for scalp patients), which account for approximately 40% of all forms of epilepsy (Semah et al 1998 ). This finding is consistent with observations previously made about the ear-EEG modality’s sensitivity to temporal lobe activity (Yarici et al 2023 ), as well as our own hypothesis that ear-EEG would be more sensitive to temporal lobe seizures given the proximity of the earbuds to the inferior and lateral temporal lobes. It is worth noting that ear-EEG also captured all 3 frontal lobe seizures (100% sensitivity), another common seizure type trailing temporal lobe seizures.…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…Further investigation of seizure types revealed that ear-EEG reliably captures temporal lobe seizures (86% for intracranial patients and 100% for scalp patients), which account for approximately 40% of all forms of epilepsy (Semah et al 1998 ). This finding is consistent with observations previously made about the ear-EEG modality’s sensitivity to temporal lobe activity (Yarici et al 2023 ), as well as our own hypothesis that ear-EEG would be more sensitive to temporal lobe seizures given the proximity of the earbuds to the inferior and lateral temporal lobes. It is worth noting that ear-EEG also captured all 3 frontal lobe seizures (100% sensitivity), another common seizure type trailing temporal lobe seizures.…”
Section: Discussionsupporting
confidence: 94%
“…This configuration results in one intra-ear channel (ELW - ELC) and two channels that span electrodes on both ears: inter-ear canal (ERW - ELW) and inter-ear diagonal (ERW - ELC). We expected the available inter-ear channels to be useful for observing laterally differential activity with high sensitivity, while the intra-ear channel was expected to elucidate activity more local to the left temporal lobe (Yarici et al 2023 ). The inter-ear diagonal channel provides largely redundant information and has been omitted from the figures presented here.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the study by Fiedler et al, the authors found that auditory attention could not be decoded with significance when only in-ear electrodes were used, even in a binaural configuration [16]. This result is to be expected, since EEG recorded from electrodes with a very small spatial separation has a very low signal-to-noise ratio (SNR) [31], [32]. Instead of using in-ear electrodes exclusively, Fiedler et al proposed to reference the in-ear electrodes to a nearby location on the scalp; the FT7 location was identified as a promising candidate.…”
Section: Introductionmentioning
confidence: 99%